TO WHAT EXTENT DOES YOUTUBE CONTENTS-BASED LANGUAGE LEARNING PROMOTE AN ENGLISH PROFICIENCY? - Dedi Aprianto (Journal of English Language Teaching and Literature (JELTL), 2020)
The flourishing development of technological software could have been as the necessary reality. The ever-changing technological learning media emergence as the description of digital disruption in educational contexts. Teaching English as a Foreign Language is regarded as a challenging activity, since language teaching is strongly expected to have a quality teaching strategies to improve English proficiency. YouTube is principally designed to increase both aspects of language competency, and personal aspects of EFL learners, such as learning motivation, critical thinking, and learning autonomy. YouTube represents the presence of the sifting educational paradigm from the traditional teaching or teacher centeredness to authentic or meaningful language learning, in which these would have been centralized on EFL learners’ domain (student-centered learning). The constructive changing of language approaches are indicated by the use of web 2.0 software presenting varying types of webs-based language learning software, YouTube. It is properly regarded to have contributed to produce the authentic and meaningful learning sources. And also, this learning model could have been made as the supplementary materials, in purpose of incorporating the traditional face-to face class activities into language learning supported by e-media. All in all, Those YouTube-based language learning’s advantages could contribute to build up independence of language learning. Therefore, the effectiveness of YouTube-based language learning potentially develop EFL learners’ class participation; social engagement, critical thinking, better comprehension of the subject-matters, and learning autonomy